FINANCIAL DISTRESS PREDICTION ANALYSIS USING ALTMAN Z-SCORE, GROVER AND ZMIJEWSKI MODELS IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2020-2023 PERIOD - Oktafiraningsih; Suryaningsum, Sri (Count : Journal of Accounting, Business and Management, 2024)
This research aims to determine whether there are differences between the Altman Z-Score, Grover and Zmijewski models in predicting financial distress and to analyze the level of accuracy of the three models. This research method is quantitative descriptive research. This research was carried out on property and real estate sector companies listed on the Indonesia Stock Exchange in 2020-2023. The data used is secondary data in the form of company financial reports. The sample for this research was 20 companies in the property and real estate sector that received special notation from the IDX. The research results show that the three models are successful in predicting the company's financial distress conditions, but there are differences in the predictions, level of accuracy and type of error for each model. The Zmijewski model has the highest accuracy rate of 83% when compared to the Grover and Altman Z-Score models